DAMPAK PANDEMI COVID-19 PADA KESEHATAN MENTAL PEMANDU WISATA DI BALI - Rahayuni, I Gusti Ayu Rai; Wulandari, Ida Ayu Putri (Jurnal Riset Kesehatan Nasional, 2021)
Background : Tour guides as individuals who experience the impact of the loss of their livelihoods need to study and analyze whether there are psychological or mental impacts that are experienced considering that they are very vulnerable to not being able to control individual coping to easily accept situations or conditions without negative impacts. This research will study and describe the extent of the impact of the Covid-19 pandemic on the mental of tour guides in Bali. Methods : Â This descriptive research with cross-sectional approach. Data was collectedÂ  from the association of tour guides in Bali in February 2021 with a total sampling technique of 115 tour guides who meet inclusion criteria. Data were collected using the Indonesian version of the SRQ-29 questionnaire online and processed by descriptive univariate. Results : The results of the study describe the conditions during the Covid-19 pandemic that 68 respondents (33.17%) had undergone a Rapid test, 45 people (21.95%) had undergone a swab test, 12 people (5.85%) had been confirmed as Positive Covid- 19 and 113 people (55.12%) stated that their area of origin or place of residence was once a red zone. The results of mental condition analysis during the pandemic showed that 134 people (65.37%) indicated symptoms of neurosis, 118 people (57.56%) indicated the use of psychoactive substances, 141 people (68.78%) indicated psychotic symptoms and that is 152 people (74.15%) indicated the presence of PTSD symptoms. Conclusion : Support from all parties through policies, attention and intervention is needed to minimize mental disorders, especially PTSD symptoms for the guides so that it is time for the Bali Return Program to start again productively without any mental obstacles.Â